2019
DOI: 10.1002/aet2.10353
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol Concentrations, Grit, and the Effect of Time

Abstract: Background: Stress is a common experience in the emergency department (ED) and is a balance of personal capabilities versus demands. Residency training is meant to improve individuals' capabilities and therefore may attenuate an individual's stress response. Grit is a personality trait that may attenuate stress in individuals. In this study we explore the relationship between time of year, postshift salivary cortisol concentrations, and the influence of grit among attendings and residents in an academic ED.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Empirical studies investigating the relationship of cortisol, alpha‐amylase and oxidative stress with grit and engagement in academic contexts are scarce and have mainly been investigated with adult samples. For example, a study of 39 residency trainees enrolled at an urban academic medical centre revealed no significant relationship between trainees’ salivatory cortisol and their status as part of the high‐ or low‐grit group (Wong et al, 2019). However, another study investigating 122 military personnel found lower cortisol levels measured in the hair of gritty individuals (Gucciardi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies investigating the relationship of cortisol, alpha‐amylase and oxidative stress with grit and engagement in academic contexts are scarce and have mainly been investigated with adult samples. For example, a study of 39 residency trainees enrolled at an urban academic medical centre revealed no significant relationship between trainees’ salivatory cortisol and their status as part of the high‐ or low‐grit group (Wong et al, 2019). However, another study investigating 122 military personnel found lower cortisol levels measured in the hair of gritty individuals (Gucciardi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is founded on the notion that as trainees gain experience in their role over the course of a year, perception of stressors and their physiologic manifestations among the trainees—as well as among the attending physicians directly responsible for them—should decrease. For example, it has been shown that the odds that an individual EP will register a detectable concentration of salivary cortisol after completing a shift significantly decrease over the course of a year [32]. An additional analysis will be restricted to the resident-only subgroup to investigate whether patterns in PR and PRV may be specific to EM trainees.…”
Section: Introductionmentioning
confidence: 99%